2007
DOI: 10.2460/javma.230.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Response of feral cats to vaccination at the time of neutering

Abstract: Results suggest that exposure to FPV, FHV, and FCV is common among feral cats and that a high proportion of cats are susceptible to RV infection. Feral cats appeared to have an excellent immune response following vaccination at the time of neutering. Incorporation of vaccination into trap-neuter-return programs is likely to protect the health of individual cats and possibly reduce the disease burden in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…18 A similar study e revealed that 48% of cats admitted to a Wisconsin animal shelter had antibodies against FPV. 5 Analyses of risk factors associated with FPV, FHV1, and FCV infections in cats in animal shelters are lacking, but results of 1 study 19 indicate that young kittens are the cats most susceptible to FPV infection and subsequent death. Thus, the prevalence of cats with antibodies against FPV in the study reported here was similar to that of unvaccinated feral cats of the other study.…”
Section: Discussionmentioning
confidence: 99%
“…18 A similar study e revealed that 48% of cats admitted to a Wisconsin animal shelter had antibodies against FPV. 5 Analyses of risk factors associated with FPV, FHV1, and FCV infections in cats in animal shelters are lacking, but results of 1 study 19 indicate that young kittens are the cats most susceptible to FPV infection and subsequent death. Thus, the prevalence of cats with antibodies against FPV in the study reported here was similar to that of unvaccinated feral cats of the other study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the immune system in older kittens is also more likely to be developed than in younger kittens, although waning maternally-derived immunity could reduce the protection afforded by age. However, a recent study documenting the response to vaccination of feral cats at the time of neutering reported that only some of the cats had protective serum antibody titers against FPV (33%), FHV (21%) and FCV (64%) (Fischer et al, 2007). It could be speculated therefore that maternally-derived immunity against these common shelter pathogens in stray kittens is not common, in part explaining the higher risk for delays on medical grounds before clearance for adoption in younger kittens.…”
Section: Discussionmentioning
confidence: 99%
“…Recent US studies have shown that cats entering shelters may be seropositive for vaccine-preventable infectious disease agents. DiGangi et al (2012) reported seropositivity for FPV (60.2%), FHV-1 (89%) and FCV (63.4%) and Fischer et al (2007) reported seropositivity for FPV (33%), FHV-1 (21%), FCV (64%) and rabies virus (3%). Seropositivity to CDV (41.2%) was less than for CPV (84.3%) in dogs entering one US shelter (Litster et al 2012) and in another study 35.5% of dogs were seropositive to both CDV and CPV, 7.7% to CDV only, 31.5% to CPV only and 25.3% to neither virus (Lechner et al 2010).…”
Section: Vaccination Of Dogs and Cats In The Shelter Environmentmentioning
confidence: 99%